A comparison of methods for adjusting biomarkers of iron, zinc, and selenium status for the effect of inflammation in an older population: a case for interleukin 6. Issue 6 (14th May 2018) - MacDonell, Sue O; Miller, Jody C; Harper, Michelle J; Reid, Malcolm R; Haszard, Jillian J; Gibson, Rosalind S; Houghton, Lisa A
ABSTRACT: Background: Older people are at risk of micronutrient deficiencies, which can be under- or overestimated in the presence of inflammation. Several methods have been proposed to adjust for the effect of inflammation; however, to our knowledge, none have been investigated in older adults in whom chronic inflammation is common. Objective: We investigated the influence of various inflammation-adjustment methods on micronutrient biomarkers associated with anemia in older people living in aged-care facilities in New Zealand. Design: Blood samples were collected from 289 New Zealand aged-care residents aged >65 y. Serum ferritin, soluble transferrin receptor (sTfR), total body iron (TBI), plasma zinc, and selenium as well as the inflammatory markers high-sensitivity C-reactive protein (CRP), α1 -acid glycoprotein (AGP), and interleukin 6 (IL-6) were measured. Four adjustment methods were applied to micronutrient concentrations: 1 ) internal correction factors based on stages of inflammation defined by CRP and AGP, 2 ) external correction factors derived from the literature, 3 ) a regression correction model in which reference CRP and AGP were set to the maximum of the lowest decile, and 4 ) a regression correction model in which reference IL-6 was set to the maximum of the lowest decile. Results: Forty percent of participants had elevated concentrations of CRP, AGP, or both, and 37% of participants had higher than normal concentrations of IL-6. Adjusted geometric mean values for serum ferritin, sTfR, and TBI were significantly lower ( P < 0.001), and plasma zinc and selenium were significantly higher ( P < 0.001), than the unadjusted values regardless of the method applied. The greatest inflammation adjustment was observed with the regression correction that used IL-6. Subsequently, the prevalence of zinc and selenium deficiency decreased (–13% and –14%, respectively; P < 0.001), whereas iron deficiency remained unaffected. Conclusions: Adjustment for inflammation should be considered when evaluating micronutrient status in this aging population group; however, the approaches used require further investigation, particularly the influence of adjustment for IL-6.